Variable Thyroid-Stimulating Hormone Dynamics in ‘Silent’ Thyrotroph Adenomas - Nigel Glynn, MB; Anne Marie Hannon, MB; Michael Farrell, MD; Francesca Brett, MD; Mohsen Javadpour, MD; Amar Agha, MD (AACE Clinical Case Reports, 2016)
ABSTRACT: Objective: Pituitary adenomas that produce thyroid-stimulating hormone (TSH) are typically accompanied by hyperthyroxinemia and a non-suppressed or elevated TSH at diagnosis. Occasionally, patients with this type of tumor have normal thyroid function test results, a condition termed ‘silent’ thyrotroph adenomas. This report characterizes TSH dynamics in this rare pituitary tumor subtype.Methods: We report 2 cases of pituitary macroadenoma associated with visual failure and hypopituitarism. The patients had normal thyroid function test results but the adenoma was intensely immunopositive for β-TSH expression. The results of TSH dynamics are reported for both cases.Results: Preoperative assessment did not reveal any clinical or biochemical evidence of pituitary hormone excess save mild, asymptomatic hyperprolactinemia consistent with pituitary stalk compression. In particular, thyroid function test results were within normal ranges. In both cases, each patient's vision recovered following transsphenoidal surgery. Histological analysis confirmed pituitary adenoma with extensive immunopositivity for TSH and the complete absence of immunostaining for all other anterior pituitary hormones. Following surgery, thyroid function test results were again normal. Surveillance magnetic resonance imaging performed 6 months postoperatively showed the presence of an intrasellar tumor remnant. A postoperative thyrotropin-releasing hormone test yielded a discordant, dynamic TSH response that was normal in one patient but was abnormal and flat in the second patient.Conclusion: TSH dynamics in ‘silent’ thyrotroph adenomas are variable. It is not known whether the biochemical behavior of the tumor may be indicative of its natural history or response to treatment.Abbreviations: ACTH = adrenocorticotrophic hormone GH = growth hormone T4 = thyroxine TRH = thyrotropin-releasing hormone TSH = thyroid-stimulating hormone